Proprioceptive Sensation Levels of The Elbows of Physically Disabled Athletes - Yildiz, Muhammed; Çebi, Mehmet (Sportverletzung · Sportschaden, 2024)
The aim of this study was to compare elbow joint proprioception measurements between physically disabled individuals who are active in sports and those who are not. The study included 30 athletes, 30 sedentary individuals, 30 physically disabled athletes, and 30 physically disabled sedentary individuals as volunteers. Elbow joint proprioception measurements were conducted using a sensitive digital goniometer with a precision of 1 degree. The joint position sense test method was used to perform the active angle repetition technique. Target angles were determined to be 30°, 60°, and 120°. A significant difference was observed in the comparison of proprioception between the dominant and non-dominant elbow joints of athletes and physically disabled sedentary individuals (p<0.05). Elbow joint proprioception was found to be highest in physically disabled athletes at the target angles. Conversely, the lowest elbow joint proprioception levels were found in physically disabled sedentary patients compared with the other groups.
Keywords: Elbow; Joint; Physically Disabled; Proprioception; Sport